Risk Factors of Asthma Among Children Attending Mosul Hospitals - Abdalwahed, Abdalwahed Maher (Journal of medical and pharmaceutical sciences, 2019)
Background: Asthma is a inflammatory condition of the lung airways resulting in episodic airflow obstruction. Symptoms are produced by irritation of small airways and may include bronchial hyper responsiveness, coughing, mainly at night or early morning. The mutable airflow obstruction is often adjustable, either spontaneously or by management . Objective: to find possible etiological risk factors and their links to Children asthma. Methods: This case-control study was conducted in four pediatric teaching hospitals for the period extending from 1st of April to end of November 2018. A total of 300 children > 15years were chosen randomly from the pediatric outpatient clinic, and divided in two group. Group A : one hundred fifty asthmatic patients were labeled as asthmatic . Group B : one hundred fifty children were matched to group A by age, sex, the group B without any history of asthma. Inclusion criteria for Group A were: Diagnosed as asthmatic by consultant pediatrician and should be respond well to anti asthmatic medication. Inclusion criteria for Group B were: Healthy or apparently healthy and without any history of medical problem or chronic diseases. Any child who is not accompanied by his /her mother or relative, and who didn’t meet the selection criteria for the A and B groups will be excluded from the study . Results: After adjusting for possible cofounders; the study showed the factors which had significant association with childhood asthma were parent consanguinity 54%(P<0.001), low educational level of parents 63%, 58% (P<0.001), small house room 65% (P<0.001), presence of animals in the home57%(P<0.001), family history of asthma72% (P<0.001), , mother disease and medications 56%(P<0.001), household exposure 69% (P<0.001), respiratory infection during infant stage 81%(P<0.001) bottle feeding74%(P<0.001) . Conclusion: The independent risk factors after adjusting was were parent consanguinity, low educational level of parents, small house room, presence of animals in the home, family history of asthma, mother disease and drugs use through pregnancy, household exposure, recurrent respiratory infection during 1st year of life. Exclusive breast feeding (1st 6 months) appeared to be protective from asthma.